Harm reduction: When does it improve health, and when does it backfire? - John H. Cawley; Davide Dragone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
Some harm reduction strategies encourage individuals to switch from a harmful addictive good to a less harmful addictive good. This approach is controversial, with advocates claiming it helps switching to a less harmful substance, and opponents claiming it may lead to new substance abuse. This paper builds on theories of addiction to model the introduction of a harm reduction method, and it demonstrates when each side is correct, depending on the enjoyableness of the harm reduction method, the addictiveness of the harm reduction method, and the substitutability with the original addictive good.
Keywords: I12; I18; D11; 330; addiction; harm reduction; initiation; moral hazard; Peltzman effect; risk compensation